2021
DOI: 10.1039/d1gc03056f
|View full text |Cite
|
Sign up to set email alerts
|

One-pot biocatalytic synthesis of nylon monomers from cyclohexanol usingEscherichia coli-based concurrent cascade consortia

Abstract: We developed a multienzyme biocatalytic cascade with high atom efficiency and a self-sufficient redox network for the synthesis of nylon monomers without adding auxiliary enzymes to recycle cofactors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…We have previously reported on using carboxylic acid reductase (CAR) for amide bond formation by intercepting the adenylate intermediate by substituting the NADPH cofactor for an amine nucleophile [17] . Others have shown that CARs are also capable of lactam formation [18] . Subsequently, it was found that using a truncated construct of CAR, consisting of a stand‐alone adenylation domain (CAR mm ‐A), was more effective in amide bond formation, and optimization of this process allowed for the selective mono‐acylation of symmetrical diamines [19] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported on using carboxylic acid reductase (CAR) for amide bond formation by intercepting the adenylate intermediate by substituting the NADPH cofactor for an amine nucleophile [17] . Others have shown that CARs are also capable of lactam formation [18] . Subsequently, it was found that using a truncated construct of CAR, consisting of a stand‐alone adenylation domain (CAR mm ‐A), was more effective in amide bond formation, and optimization of this process allowed for the selective mono‐acylation of symmetrical diamines [19] .…”
Section: Figurementioning
confidence: 99%
“…[17] Others have shown that CARs are also capable of lactam formation. [18] Subsequently, it was found that using a truncated construct of CAR, consisting of a stand-alone adenylation domain (CARmm-A), was more effective in amide bond formation, and optimization of this process allowed for the selective mono-acylation of symmetrical diamines. [19] A recent study showed that CARs are also capable of ester formation.…”
mentioning
confidence: 99%
“…HI-31 with ADH and CHMO in one E. coli cell that could also catalyze the transformation of CL to HHA. 60…”
Section: -Hydroxyhexanoic Acid (Hha)mentioning
confidence: 99%
“…Recently, another cascade reaction of CHOL to ACA was reported 60 and an aldehyde reductase (AHR) from Synechocystis species was used for the direct conversion of HHA to ACA without in situ capping of inhibitory carboxyl group in E. coli (Scheme 8(ii)). Unlike prim-ADH, the activity of AHR was not inhibited by the free carboxylic acid group of HHA.…”
Section: -Aminocaproic Acid (Aca)mentioning
confidence: 99%
See 1 more Smart Citation